Pentingnya Soft Skill dalam Membangun Jiwa Kepemimpinan - Angelica Fajar Pitaloka; Jullia Ivanna (Sekolah Tinggi Agama Islam Sumatera Medan, 2018)
This study aims to find out how the Soft Skill Head of Village Helvetia Sunggal District Deli Serdang. The method used in this research is quantitative descriptive method, which is presented in the form of observation and spreading of questionnaire. The population in this study is the entire community of the village of Helvetia is 4,462 Head of Family consisting of 8 Hamlet. Sampling technique in this research is by using purposive sampling technique, this sampling technique based on certain purpose by considering and considering the availability of researcher, time, and object of research to be researched or very wide data source hence sampling is by category of sample determination that is Dusun I with the smallest number of 392 families and Dusun VI with the largest number of citizens 720 families, by taking 10% from each sample that is Dusun I as many as 39 families and Dusun VI 72 KK, so that the sample used is 111 Head of Family. Analytical techniques that the authors use in this study by describing according to percentage or translated through frequency tables. The result of the research shows that the soft skill of the Head of Helvetia Village, Sunggal Sub-district, Deli Serdang Regency are good enough, it can be seen from the result of research indicating that the soft skill indicators are competence (knowledge and skill) 91.25%, empathy 83.33% integrity of 73.66%, firmly 89.66% and 93.5% of the authority with an average total of 86.28% of the public said that the Head of Helvetia Village has good personal qualities in him so as to be capable and quite successful in realizing and creating public confidence in the figure of the Head of the Village through the results of its performance.